The Influence of Leadership Style and Organizational Culture by Mediating Job Satisfaction on Organizational Commitment Case Study in Employees Of Islamic Education Institution - Fatmah Bagis; Akhmad Darmawan; Arini Hidayah; Mastur Mujib Ikhsani (Jurnal Ilmiah Ekonomi Islam, 2020)
Abstract - This study aims to describe the influence of leadership style and organizational culture with the mediating variables of job satisfaction on organizational commitment. This study uses a case study method for employees of educational institutions in Purwokerto. Respondents in this study were 74 employees from management level to staff level. PLS (Partial Least Square) analysis using SmartPLS 3.0 is the analysis technique used in this study. The results obtained are first, Leadership Style has no significant effect on Job Satisfaction. Second, Organizational Culture has a significant effect on Job Satisfaction, and Third, Job Satisfaction has a significant effect on Organizational Commitment. Based on the research results prove that Job Satisfaction can only mediate the relationship between Organizational Culture and Organizational Commitment while the relationship between Leadership Style and Organizational Commitment cannot be mediated by Job Satisfaction. Keywords: leadership style, organizational culture, job satisfaction, organizational commitment